A comparison of Kawasaki Disease and multisystem inflammatory syndrome in children. (June 2022) - Wessels, Philip A.; Bingler, Michael A.
Abstract: Background: Due to the COVID-19 pandemic a novel disease has emerged, multisystem inflammatory syndrome in children (MIS-C). It presents post virally after a COVID-19 infection, and its clinical presentation and symptoms are very similar to Kawasaki Disease (KD). Aim of review: The objective of this review is to compare and contrast differences of Kawasaki Disease and MIS-C. Key scientific concepts of the review: Kawasaki Disease and MIS-C are very similar in clinical presentation and symptomatology. Understanding the diagnostic criteria is crucial to making an accurate diagnosis. Treatments in Kawasaki Disease are established, while in MIS-C treatment protocols are continuing to develop. Careful history taking and laboratory marker analysis should guide the clinician to accurate diagnosis. Highlights: MIS-C and KD present similarly, and this is a challenge diagnostically. Laboratory markers help differentiate MIS-C and KD. IVIG is used in treatment of both KD and MIS-C. KD has well established treatment protocols, whereas MIS-C treatment protocols are still evolving. Cardiac involvement is present in both KD and MIS-C.